Observations of air–sea heat fluxes in the southwestern Atlantic under high‐frequency ocean and atmospheric perturbations. (6th October 2020) - Santini, M. F.; Souza, R. B.; Pezzi, L. P.; Swart, S.
Abstract: Turbulent air–sea heat fluxes were computed from in situ high‐frequency micrometeorological data during two research cruises performed in the southwestern Atlantic Ocean (SWAO) occurring in June 2012 and October 2014. Two different and dynamical areas were covered by the cruises: the Brazil‐Malvinas Confluence (BMC) and the Southern Brazilian Continental Shelf (SBCS). The eddy covariance (EC) method was used to estimate the air–sea sensible‐ and latent‐heat fluxes. This article compares these novel high‐frequency estimates of heat fluxes with bulk parametrizations made at the same location and time from independent measurements taken on board the ships. When comparing the EC and bulk‐estimated time series of sensible‐heat fluxes, we found a good agreement both in their magnitude and variability, with small bias (generally <20 W·m −2 ) between the datasets from the two study areas in the SWAO. However, the EC and bulk latent‐heat flux comparisons show large biases ranging from 75 W·m −2 to 100 W·m −2 in the SBCS and BMC, respectively. These biases were always associated with short‐term, high‐frequency environmental perturbations occurring either in the atmosphere or in the ocean with the majority related to strong wind burst events and large air–sea temperature gradients. The short period changes in atmospheric conditions were mostly related to the passage of transient synoptic systems over the two study areas. The large air–sea temperature gradients were mostly linked to the surface characteristics of the BMC and SBCS regions, where sharp oceanographic fronts are located. Our results are able to contribute to improving weather and climate simulations of the mid‐ to high latitudes of South America, a region largely influenced by the sea‐surface temperature patterns of the SWAO in combination with the frequent propagation of transient atmospheric systems. Abstract : Novel data from two research cruises performed in the southwestern Atlantic Ocean were used to describe the ocean–atmosphere latent‐ and sensible‐heat fluxes. We found that these heat fluxes were modulated by high‐frequency environmental changes in the atmosphere or in the ocean such as episodes of strong wind bursts, transient systems passage, or large differences between the SST and the air temperature at sea level.